Rare serotype adenoviral vectors for HIV vaccine development - Michael, Nelson L. (American Society for Clinical Investigation, 2011)
Human adenoviral vectors are being developed for use in candidate vaccines for HIV-1 and other pathogens. However, this approach suffered a setback when an HIV-1 vaccine using an adenovirus type 5 (Ad5) vector failed to reduce, and might even have increased, the rate of HIV infection in men who were uncircumcised and who had preexisting antibodies specific for Ad5. This increased interest in the evaluation of serologically distinct adenoviral vectors. In this issue of the JCI, Frahm and coworkers report evidence that preexisting cellular immune responses directed toward Ad5 reduce the immunogenicity of antigens expressed in Ad5-vectored vaccines and have cross-reacting potential with non-Ad5 adenoviral vectors. The implications of this observation need to be carefully evaluated in future clinical trials of all serotypes of adenovirus-vectored vaccines.